10 RADIOLOGICAL ANATOMY OF THE HEART AND MEDIASTINUM IN ELECTROSTIMULATION: A GUIDE FOR TSRM, NURSES AND TFCPC. (15th December 2022) - Santucci, Stefano; Santucci, Matteo
Abstract: For the implantation of the PM, iodized contrast medium is rarely used and to recognize the anatomical structures within which one is operating, one must resort to the interpretation of only the radiological images obtained with the use of ionizing radiation. To verify the correct positioning of the leads, it is necessary to have multiple points of view (projections). Confirmation is usually sought with at least two projections that are almost orthogonal to each other. The fluoroscopic visualization shows a two-dimensional antomy typical of radiological imaging and we speak of a cardiac shadow formed by the overlapping of all vascular structures Typical views to visualize correct lead placement require multiple views, usually two. The projections RAO 20-25 ° and LAO 25-30 ° are almost orthogonal. With the first, the cardiac silhouette shows the right ventricle in its maximum longitudinal extension. With the LAO, the left ventricle and the right ventricle are represented paired with a view comparable to the 4-chamber ultrasound imaging Knowledge of radiological anatomy is very important in determining the correct positioning of the leads.